Pengaruh Variasi Konsentrasi NaOH Terhadap Analisis Hilang Pijar dan Kehalusan Butiran Semen Geopolimer Berbasis Tanah Napa Lintau - Saputra, Fajri Rahmat (RC-INSTITUT, 2019)
This research was conducted to understand the benefits of napa soil as main material in geopolymer cement synthesis. Napa soil used obtained from Lintau Tanah Datar district is natural material containing Al2O3 and SiO2 as the main chemical componens which is usually used by thepeople of  West Sumatera as traditional medicine for stomach ache and diarrhea. The characteristics of napa soil based geopolymer cement which are influenced by variation in the concentration of sodium hydroxide ( 10M, 12 M, 14M, 16M ) was observed in this study. The chacateristics of geopolymer cement concists of fineness of cement particle and the lost of ignition. The results of this study indicate that the fineness value of cement particle and the lost of ignition of geopolymer cement complied the indonesian standards of cement   (SNI 2049:2015). The optimum concentration of sodium hydroxide is 16 M. The increasing in the concentration of sodium hydroxide increase the value lost of ignition of geopolymer cement.